Standarization for a Peruvian Version of The Functional Incapacity Index in The Health Assessment Questionnaire (HAQ) - Grave, Carlos (1996)
Objective: Standarization of a Peruvian version for the functional incapacity Index of the Health Assessment Questionaire (HAQ). Material and Methods: Forty one patients with Rheumatoid Arthritis, from 3 different Hospitals of Lima, were evaluated. All of them underwent HAQ, previously translated to a Spanish Peruvian version. Then we compared the results by direct observation, done by a blind researcher, of 12 activities. Statistical analysis: The coefficient of correlation of Pearson was applied. Results: The mean of the HAQ was 0.50 (scale 0-3) range 0.00-1.87, of observed incapacity was 0.45 (0.00 - 1.58) (r0.86, p<0.0001). Conclusion: There is a good correlation between referred and observed functional incapacity. With some modifications the Functional Incapacity Index of the Peruvian version of the HAQ should be applied to more Peruvian patients with with RA, for a long-term, for further validation.